Anterior Compartment Sparing Tibial Tubercle Osteotomy Using Back-Cut Technique - Raahil Patel, M.D.; Richard J. Rivera, B.S.; Sunny Parekh, D.O.; Brandon Cabarcas, M.D.; Brent Hill, M.D.; Rachel Carlson, P.A.-C.; Neil Kumar, M.D., M.B.A. (Arthroscopy Techniques)
Tibial tubercle osteotomy (TTO) is a surgical technique commonly indicated for patellofemoral instability and/or patellar chondral repair. In select patients, soft tissue procedures alone (medial patellofemoral ligament reconstruction) are not sufficient to address patellar instability due to significant bony malalignment, particularly in patients with a >20-mm tibial tubercle-trochlear groove distance on advanced imaging. For these cases, a TTO procedure may be used either in adjunct to medial patellofemoral ligament reconstruction or in isolation. Among the postoperative complications of TTOs, compartment syndrome poses a threat as one of the most severe. In this Technical Note, we present a technique that aims to reduce the risk of postoperative compartment syndrome by eliminating dissection of the anterior compartment musculature during the approach.